Una perspectiva de la historiografía bíblica: de acuerdo a un concepto de la naturaleza teológica de la Biblia - Quiroga, Raúl (DavarLogos, 2008)
In this article there will be presented a perspective between biblical historiography in the context of the enlightenment of the ancient historiography which evokes the framework of the actual discussion between each other.The Bible is independent form any extra-biblical information related to it. Its theological macro-structure or the whole message of the Word of God to his people is inalterable. On other hand, its micro-structure or superficial area may be modified by external historical evidence in benefit of its comprehension.